CYCLIC COUPLED FIXED POINT THEOREM IN COMPLEX VALUED METRIC SPACES - KUMAR*, T. SENTHIL; PALANIAPPAN, Y.; HUSSAIN, R. JAHIR (International Journal of Mathematical Archive, 2018)
In this paper we prove a strong cyclic coupled fixed point theorem for Kannan type contractions in complex valued metric spaces.Â